Effect of organic fertilizers on nutrients content and essential oil composition of savory (Satureja hortensis L.) - Behrooz Esmaielpour; Mahdi Rahmanian; Surur Khorramdel; Hojjat Gharavi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2018)
Application of organic fertilizers in the production of plants is aimed to eliminate or substantially reduce the use of chemical inputs and improve the growth and quality of plants. For instance, in present study, the effect of vermicompost and spent mushroom compost application on nutritional status and essential oil components of summer Savory (Saturejahortensis L.) was investigated. This experiment was conducted in the research greenhouse of Faculty of Agriculture at Mohaghegh Ardabili University using a layout of completely randomized design with five replications on Savory in 2014. Experimental treatments included different substrates that contained vermicompost, washed and unwashed spent mushroom compost in five levels (10, 20, 30, 40 and 50 Percent v/v). After flowering, the plants were harvested and parameters such as leaf area, leaf and plant dry weight, chlorophyll index of leaf and N, P, K, and Ca content and essential oil component of plants were measured. The results showed that the effect of organic substrates on macronutrient content and savory’s growth parameters was significant. The highest Nitrogen content (6.3%) and Phosphorus (0.98%) in savory shoot was obtained in a substrate supplemented with 40% vermicompost. Plants grown in the media containing 30% of vermicompost and 50% of washed spent mushroom compost (SMC) have higher potassium (3.19%) and calcium (2.48%) content, respectively. The lowest nitrogen, phosphorus and potassium content in the aerial part was obtained in the control treatment. Moreover, application of organic fertilizers significantly affected on savory’s essential oil percentage and compounds composition. The highest and lowest essential oil contents were obtained in plants in substrates containing 30 % of vermicompost and unwashed spent mushroom compost respectively. The main components of essential oil were carvacrol and gamma-trepenine. The highest level of carvacrol (62.10) and gamma-trepenine (32.05) were obtained in plants in substrates containing 40 and 20% of washed spent mushroom respectively.